2023
DOI: 10.1021/acsnano.3c01523
|View full text |Cite
|
Sign up to set email alerts
|

How Regiochemistry Influences Aggregation Behavior and Charge Transport in Conjugated Organosulfur Polymer Cathodes for Lithium–Sulfur Batteries

Abstract: For lithium–sulfur (Li–S) batteries to become competitive, they require high stability and energy density. Organosulfur polymer-based cathodes have recently shown promising performance due to their ability to overcome common limitations of Li–S batteries, such as the insulating nature of sulfur. In this study, we use a multiscale modeling approach to explore the influence of the regiochemistry of a conjugated poly­(4-(thiophene-3-yl)­benzenethiol) (PTBT) polymer on its aggregation behavior and charge transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 111 publications
0
11
0
Order By: Relevance
“…PTBT as an organosulphur cathode on its aggregation behaviour and charge transport (Figure 4b) [26]. The morphology of a polymer can significantly affect its conductive behaviour.…”
Section: Schütze Et Al Investigated the Effect Of The Regiochemistry ...mentioning
confidence: 99%
“…PTBT as an organosulphur cathode on its aggregation behaviour and charge transport (Figure 4b) [26]. The morphology of a polymer can significantly affect its conductive behaviour.…”
Section: Schütze Et Al Investigated the Effect Of The Regiochemistry ...mentioning
confidence: 99%
“…Also, there is no commonly accepted equilibration method due to the rather different microstructures of SCPs, e.g., from semicrystalline polymers to amorphous glasses, and the wide range of glass-transition temperature T g (or melting points) for different SCPs . With respect to the third step, many alternatives are available including semiempirical, , tight binding, , and DFT methods, , which reduce the comparability between different works. The aforementioned inhomogeneities and implemental difficulties resulted in studying a limited number of models, i.e., only a few high-quality polymer models per investigation have been possible. , Thus, having fewer models studied and incomparable models generated in different studies has obstructed the development of structure–electronic property relationships required for formulating SCP design rules.…”
Section: Introductionmentioning
confidence: 99%
“…The thiophene ring in TBT acts as the conjugated backbone, while benzenethiol is the organosulfur-based side chain. In recent work, some of us have shown that out of different regioregularities of thiophene groups, a head-to-tail/head-to-tail regularity leads to a crystalline phase, while a head-to-head/tail-to-tail regularity shows no long-range order …”
Section: Introductionmentioning
confidence: 99%